Maternity leave in the context of couples: The impact of both partners' characteristics and employment experiences on mothers' re-entry into the labour market - Stefanie Hoherz (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This research focuses on re-entry for mothers after maternity leave. The empirical analysis focuses on the first twenty-two years of post-reunification Germany, using proportional hazards models. Results show that the re-entry into part-time employment is primarily affected by the mothers own resources and former career, the return to full-time work is more linked to the partners resources. This behaviour is especially prevalent in families where the mother has a higher earning potential than the father, a group having the highest re- entry chances for mothers, especially into full-time employment. The results concerning experiences of unemployment for the male partner show that mothers try to compensate uncertainties with increased labour force participation.
Keywords: D13; J22; J64; 330; maternal employment; added-worker effect; proportional hazard; Germany